The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1515/bhk-2017-0025
|View full text |Cite
|
Sign up to set email alerts
|

Balance in children born prematurely currently aged 6–7

Abstract: SummaryStudy aim: Premature birth is one of the major problems of obstetrics, leading to numerous complications that are associated with prematurity, for instance balance disorders. The aim of the study was to assess the impact of premature birth on the ability to maintain balance in children commencing their school education. Material and methods:The study included children aged 6-7 years. The study group consisted of 59 children (31 girls and 28 boys, mean age 6.38 ± SD 0.73) born prematurely between 24 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 36 publications
0
16
1
Order By: Relevance
“…On the other hand, balance was evaluated in seven studies ( 23 28 , 30 , 31 ), the children included in these studies had ages from three years. Dziuba et al ( 24 ) and Silva et al ( 26 ) did not find significant differences, and Rodríguez et al ( 25 ) did not find significant results for stabilometry except for the closed-eyes condition and over a viscoelastic foam surface (which were worse for the preterm group), but they did find significant differences for MABC-2. The study by Bucci et al ( 23 ), which considered the surface and the average speed of the centre of pressure (CoP), obtained worse result for the preterm infants group; whereas Petersen et al ( 27 ) showed by means of posturography worse results in the active and reactive postural stability of the preterm group with open and closed eyes in an anteroposterior direction and with open eyes in a lateral direction.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…On the other hand, balance was evaluated in seven studies ( 23 28 , 30 , 31 ), the children included in these studies had ages from three years. Dziuba et al ( 24 ) and Silva et al ( 26 ) did not find significant differences, and Rodríguez et al ( 25 ) did not find significant results for stabilometry except for the closed-eyes condition and over a viscoelastic foam surface (which were worse for the preterm group), but they did find significant differences for MABC-2. The study by Bucci et al ( 23 ), which considered the surface and the average speed of the centre of pressure (CoP), obtained worse result for the preterm infants group; whereas Petersen et al ( 27 ) showed by means of posturography worse results in the active and reactive postural stability of the preterm group with open and closed eyes in an anteroposterior direction and with open eyes in a lateral direction.…”
Section: Resultsmentioning
confidence: 92%
“…All the studies included underage participants, who were classified according to gestational age, regardless of birth weight and sex. Out of the 16 studies, eight provided the average gestational age per group ( 19 21 , 23 , 28 , 29 , 31 , 32 ); seven provided the intervals of gestational age which corresponded to each group ( 18 , 22 , 24 27 , 30 ), and one provided the data about the average gestational age of the preterm group, even though it did not provide data referring to the control group ( 33 ). The birth weight and sex of both groups was specified in 10 studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Preterm children are more likely to have learning disabilities and poor school performance [65]. Premature birth affects the ability to maintain body balance [21]. Parental involvement is essential in the preventive treatment of a child's sensomotoric, social-emotional and cognitive-linguistic development [74].…”
Section: Discussionmentioning
confidence: 99%